The Biogeographical Distribution of Benthic Roseobacter Group Members along a Pacific Transect Is Structured by Nutrient Availability within the Sediments and Primary Production in Different Oceanic Provinces - Pohlner, Marion; Degenhardt, Julius; von Hoyningen-Huene, Avril J. E.; Wemheuer, Bernd; Erlmann, Nora; Schnetger, Bernhard; Badewien, Thomas H.; Engelen, Bert (Frontiers in Microbiology, 2017)
By now, only limited information on the Roseobacter group thriving at the seafloor is available. Hence, the current study was conducted to determine their abundance and diversity within Pacific sediments along the 180° meridian. We hypothesize a distinct biogeographical distribution of benthic members of the Roseobacter group linked to nutrient availability within the sediments and productivity of the water column. Lowest cell numbers were counted at the edge of the south Pacific gyre and within the north Pacific gyre followed by an increase to the north with maximum values in the highly productive Bering Sea. Specific quantification of the Roseobacter group revealed on average a relative abundance of 1.7% and 6.3% as determined by catalyzed reported deposition-fluorescence in situ hybridization (CARD-FISH) and quantitative PCR (qPCR), respectively. Corresponding Illumina tag sequencing of 16S rRNA genes and 16S rRNA transcripts showed different compositions containing on average 0.7% and 0.9% Roseobacter-affiliated OTUs of the DNA- and RNA-based communities. These OTUs were mainly assigned to uncultured members of the Roseobacter group. Among those with cultured representatives, Sedimentitalea and Sulfitobacter made up the largest proportions. The different oceanic provinces with low nutrient content such as both ocean gyres were characterized by specific communities of the Roseobacter group, distinct from those of the more productive Pacific subarctic region and the Bering Sea. However, linking the community structure to specific metabolic processes at the seafloor is hampered by the dominance of so-far uncultured members of the Roseobacter group, indicating a diversity that has yet to be explored.